Novel anti-CD73-IL-2v bispecific fusion protein augments antitumor immunity by alleviating immunosuppressive adenosine pathways in CD8+ T cells - Kyungwha Lee; Jung-Yun Lee; Ji-Hyun Kim; Min Park; Junsik Park; Young Min Oh; Wonjae Lee; Myoung Ho Jang; Young Jun Koh; Sanghee Lee; Jisoo Kim; Kayoung Shin; et al. (Journal for ImmunoTherapy of Cancer)
Background Adenosine accumulated in the tumor microenvironment functions as an immune-modulating factor, exerting immunosuppressive actions via adenosine A2A/A2B receptor (A2AR/A2BR) in various immune cell types. CD73, a key enzymatic regulator responsible for adenosine production, is frequently overexpressed in diverse cancers, and its overexpression is associated with reduced responsiveness to conventional anti-cancer drug treatments such as chemotherapy, radiation therapy, targeted therapy, or immunotherapy. Despite numerous therapeutic applications of IL-2 in cancer immunotherapy, the relationship between the CD73-adenosine axis and IL-2-based immunotherapy remains largely unexplored.Methods To evaluate the effect of CD73 blockade on IL-2 signaling of CD8+ T cells, we screened novel CD73 antibodies using human single-chain variable fragment phage library and immunized Alpaca phage library. To optimize targeting to CD73-expressing cells and reinvigorate the antitumor effect of IL-2 in adenosine-rich microenvironment, we engineered a novel bifunctional GI-αCD73/IL-2v fusion protein. Functionality of GI-αCD73/IL-2v fusion protein was assessed in the in vitro cell-based assays and the in vivo tumor-bearing mouse model or cynomolgus monkey.Results IL-2-induced increase in proliferation of CD8+ T cells was not observed under adenosine-rich microenvironment. We demonstrated that the functional impairment of IL-2 signaling in CD8+ T cells in these conditions can be reversed by our anti-CD73 antibody (GI-αCD73). Furthermore, GI-αCD73/IL-2v fusion protein significantly restored the impaired proliferation of CD8+ T cells and consequently enhanced tumor cell killing under adenosine-mediated immunosuppression, surpassing the combined treatment of GI-αCD73 and Fc-IL-2v. These synergistic effects were attributed to the enhanced delivery of the IL-2v component of GI-αCD73/IL-2v to IL-2Rβγ on CD73-expressing CD8+ T cells through a cis-binding mechanism. GI-αCD73/IL-2v elicited a potent antitumor effect in both the human CD73 knock-in (hCD73 KI) mouse model and the humanized mouse model. In non-human primates, GI-αCD73/IL-2v exhibited excellent tolerability while inducing robust and durable expansions of cytotoxic lymphocytes.Conclusions GI-αCD73/IL-2v bispecific protein is a novel and potent immunocytokine with significant antitumor immunity through cis-binding on CD8+ T cells.